Differences of physical fitness performance between basketball players from different competitive levels (elite and sub-elite) in the state union of Serbia and Montenegro for the 2004/2005 season - Vukasevic, V.; Bubanja, M.; Zarkovic, B.; Jabucanin, B.; Masanovic, B. (SportMont, 2021)
The purpose of this research was to describe the physical fitness of basketball players from different competitive lev- els for the 2004/2005 season and to make comparisons between them. The sample included 96 participants divided into two sub-samples; the first sub-sample comprised 48 participants who competed in the First Basketball League of Serbia and Montenegro; the second sub-sample comprised 48 participants who competed in the Second Basketball League of the State Union of Serbia and Montenegro. Standardized tests for the assessment of physical fitness perfor- mance were used. Data were analysed using SPSS software, and the descriptive statistics were expressed as a mean and standard deviation for each variable, while the t-test for small independent samples was carried out to detect the possible differences. The results showed that significant differences were found for all nine tests, and the highest differences are found in the results of sit-up and vertical jump tests. Therefore, these findings may give coaches from the region better working knowledge and help them select talented players in the best manner possible.